Majallah-i pizishkī-i dānishgāh-i ̒ulūm-i pizishkī-i Tabrīz - Dānishgāh-i ̒ulūm-i pizishkī-i Tabrīz (Tabriz University of Medical Sciences, 2021)
Devoted to research and scholarship in medical sciences
Keywords: Medicine : Periodicals : 2fast : 0(OCoLC)fst01015004; Iran